2010
DOI: 10.1097/iae.0b013e3181cd47ed
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Characteristics of Endophthalmitis After an Injection of Intravitreal Antivascular Endothelial Growth Factor

Abstract: Acute endophthalmitis following anti-VEGF injection appears within days and can result in severe loss of vision if not treated promptly. In our series the clinical and prognostic characteristics were considerably different between culture positive endophthalmitis cases and culture negative cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
40
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(42 citation statements)
references
References 20 publications
1
40
0
1
Order By: Relevance
“…In one study the time of presentation, presence of pain, and the severity of clinical findings were helpful. 26 The symptoms began at an average of 2.55 days (range, 1-6 days) after injection in the endophthalmitis group and less than 1 day in the acute intraocular inflammation group. Seven of nine patients with endophthalmitis and two of five patients with acute intraocular inflammation had a painful eye on presentation.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In one study the time of presentation, presence of pain, and the severity of clinical findings were helpful. 26 The symptoms began at an average of 2.55 days (range, 1-6 days) after injection in the endophthalmitis group and less than 1 day in the acute intraocular inflammation group. Seven of nine patients with endophthalmitis and two of five patients with acute intraocular inflammation had a painful eye on presentation.…”
Section: Methodsmentioning
confidence: 99%
“…26,27 Rhegmatogenous retinal detachment The overall incidence of rhegmatogenous retinal detachment (RRD) after intravitreal injection of anti-VEGF agents is low (0 to 0.67%). 25,29 In a study on Medicare database, the differences in rates of RRD and retinal tear were not statistically significant between eyes with intravitreal anti-VEGF injection and a matched control group.…”
Section: Methodsmentioning
confidence: 99%
“…The only statistically significant variable they found to decrease the rate of endophthalmitis was the use of topical povidone-iodine to sterilize the ocular surface [2]. Both this study and the study by Mezad-Koursh et al did not examine the use of postinjection antibiotics as an independent variable; all patients in both groups routinely received antibiotics postinjection [2][3]. It has been shown that the use of povidone-iodine on the ocular surface is just as effective as a combination of preinjection antibiotic drops along with povidone-iodine, and most ophthalmologists therefore do not use any preinjection antibiotics [8].…”
Section: Introductionmentioning
confidence: 57%
“…Of the few cases of post-injection endophthalmitis reported in the literature, there is a significant percentage that had negative cultures (33% -70%) [1][2][3]6]. Of the cases in which cultures were positive, the most common organisms were coagulase-negative Staphylococcus spe-cies, Streptococcus species, followed by Bacillus cereus, and Enterococcus faecalis [1,2].…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation